Manajemen Dakwah di Masjid Al-Falah Kertasmaya Indramayu - Yusup, Mohamad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the implementation of da'wah management at the Al-Falah Mosque in Kertasmaya, Indramayu, and the strategies for managing religious activities in response to the dynamics of modern society. The research method used was qualitative with a descriptive approach, through interviews, observation, and documentation. The results indicate that da'wah management at the Al-Falah Mosque has implemented management functions (planning, organizing, implementing, and evaluating) effectively, although challenges remain in the areas of young congregant participation and digital media utilization.